2023
DOI: 10.3390/polym15153164
|View full text |Cite
|
Sign up to set email alerts
|

Highly Enhanced Mechanical, Thermal, and Crystallization Performance of PLA/PBS Composite by Glass Fiber Coupling Agent Modification

Abstract: To improve the toughness and heat resistance of polylactic acid (PLA), polybutylene succinate (PBS) was sufficiently blended with PLA as the base matrix, and the glass fiber (GF) that was modified with 3-aminopropyltriethoxysilane (KF-GF) was added as the reinforcement. The results demonstrated a noteworthy boost in both mechanical and heat resistance properties when employing KH-GF, in comparison to pristine GF. When the content of KH-GF reached 20%, the tensile, flexural, and IZOD impact strength of the comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…The thermal softening temperature of the PLA is less (i.e., 36% less) than that of the ABS parts. Given that the softening temperature of PLA is around 60 °C (i.e., less than the temperature measured by the nozzle as shown in Figure S1), the impinging particles could experience more dispersion onto the PLA surface, resulting in a CS deposition with a relatively larger line width as compared to the ABS parts.…”
Section: Results and Discussionmentioning
confidence: 94%
“…The thermal softening temperature of the PLA is less (i.e., 36% less) than that of the ABS parts. Given that the softening temperature of PLA is around 60 °C (i.e., less than the temperature measured by the nozzle as shown in Figure S1), the impinging particles could experience more dispersion onto the PLA surface, resulting in a CS deposition with a relatively larger line width as compared to the ABS parts.…”
Section: Results and Discussionmentioning
confidence: 94%
“…Recent years have been witnessing increased usage of petroleum‐based polyolefins in the food packaging industries, which is due to their acceptable mechanical properties, cheapness, excellent processability, and so forth 1 . Nevertheless, besides the mentioned advantages, the major issue with these polymers is their long‐time decomposition 2–4 . Although developed countries spend huge amounts of money on reducing these polymeric pollutants, these methods also have many problems, including increasing the amount of greenhouse gas emissions and toxic compounds in the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, among the various biodegradable polymers such as polypeptides, cellulose, polysaccharides, chitin/chitosan, and so forth, poly (lactic acid) (PLA) has received a great deal of attention because of its acceptable physical and mechanical properties 8–11 . Some studies have indicated that PLA has a mechanical strength comparable to that of polyolefins 3,5,9 . So far, this polymer has been widely used in various industries such as medical implants, veneers, fabrics, and so forth 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Plastic waste is a serious environmental problem around the world that can be resolved by the use of biodegradable bioplastics instead of non-biodegradable petroleum-based plastics. For this purpose, poly(L-lactic acid) or poly(L-lactide) (PLLA) is an important biodegradable bioplastic for use in agricultural [1], packaging [2][3][4], sports [5], and biomedical [6] applications because of its non-toxicity, low cost, good mechanical strength, and easy processability [7][8][9]. However, the low flexibility, low toughness, slow crystallization rate, and slow biodegradation rate of PLLA limit its wide applications [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, poly(L-lactic acid) or poly(L-lactide) (PLLA) is an important biodegradable bioplastic for use in agricultural [1], packaging [2][3][4], sports [5], and biomedical [6] applications because of its non-toxicity, low cost, good mechanical strength, and easy processability [7][8][9]. However, the low flexibility, low toughness, slow crystallization rate, and slow biodegradation rate of PLLA limit its wide applications [9][10][11][12][13]. In our previous works [14][15][16], block copolymerization was used to prepare poly(L-lactide)-b-poly(ethylene glycol)-b-poly(L-lactide) (PLLA-PEG-PLLA) block copolymers, which showed a higher flexibility, higher toughness, faster crystallization rate, and faster biodegradation rate than the PLLA due to the flexibility and hydrophilicity of PEG middle-blocks.…”
Section: Introductionmentioning
confidence: 99%